Inflation Targeting vs. Price level Targeting : Comparison in the DSGE Model - Ježek, Jan; Potužák, Pavel; Chytilová, Helena; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2023)
This thesis compares inflation targeting and price level targeting in the NK DSGE model. The previous decade was marked by low inflation and zero nominal interest rates. Therefore, there has been a renewed discussion of alternative regimes, including price level targeting. It is inflation targeting and price level targeting that are examined in a DSGE model incorporating wage and price rigidities. The regimes are examined in a situation without the ZLB. It is shown that in most situations PLT exhibits lower variability in inflation and output. Next, I conduct a welfare analysis. Here again (flexible) price level targeting emerges as the best. Last, consumption equivalence was performed to quantify the differences between regimes. Overall, price level targeting appears to be the better regime, but the differences between PLT and IT are not very large.
Vedoucí práce: Pavel Potužák
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: ekonomie [obor dipl. práce]; diplomové práce; master's theses